Exfoliative cytology for the diagnosis of basal cell carcinoma and other skin cancers in adults - Ferrante di Ruffano, Lavinia; Dinnes, Jacqueline; Chuchu, Naomi; Bayliss, Susan E.; Takwoingi, Yemisi; Davenport, Clare; Matin, Rubeta N.; O'Sullivan, Colette; Roskell, Derek; Deeks, Jonathan J.; Williams, Hywel C. (Wiley, 2018)
Background: Early accurate detection of all skin cancer types is essential to guide appropriate management and to reduce morbidity and improve survival. Basal cell carcinoma (BCC) is usually localised to the skin with potential to infiltrate and damage surrounding tissue, while cutaneous squamous cell carcinoma (cSCC) and melanoma have a much higher potential to metastasise and ultimately lead to death. Exfoliative cytology is a non–invasive test that uses the Tzanck smear technique to identify disease by examining the structure of cells obtained from scraped samples. This simple procedure is a less invasive diagnostic test than a skin biopsy, and for BCC has the potential to provide an immediate diagnosis that avoids an additional visit to clinic to receive skin biopsy results. This may benefit patients scheduled for either Mohs micrographic surgery or non–surgical treatments such as radiotherapy. A cytology scrape can never give the same information as a skin biopsy, however, so it is important to know more about which skin cancer situations it may be helpful. Objectives: The primary objective was to determine the diagnostic accuracy of exfoliative cytology for the detection of basal cell carcinoma (BCC) in adults. Secondary objectives were to determine diagnostic accuracy for the detection of i) cutaneous squamous cell carcinoma, ii) invasive melanoma and atypical intraepidermal melanocytic variants, and iii) any skin cancer, including keratinocyte skin cancer, invasive melanoma and atypical intraepidermal melanocytic variants, or any other skin cancer. Search methods: We undertook a comprehensive search of the following databases from inception up to August 2016: Cochrane Central Register of Controlled Trials; MEDLINE; EMBASE; CINAHL; CPCI; Zetoc; Science Citation Index; US National Institutes of Health Ongoing Trials Register; NIHR Clinical Research Network Portfolio Database; and the World Health Organization International Clinical Trials Registry Platform. We also studied the reference lists of published systematic review articles. Selection criteria: Studies evaluating exfoliative cytology in adults with lesions suspicious for BCC, cSCC or melanoma, compared with a reference standard of histological confirmation. Data collection and analysis: Two review authors independently extracted all data using a standardised data extraction and quality assessment form (based on QUADAS-2). Where possible we estimated summary sensitivities and specificities using the bivariate hierarchical model. Main results: This review reports on nine studies with a total of 1655 lesions including 1120 BCCs (14 datasets), 401 lesions with 44 cSCCs (two datasets), and 200 lesions with 10 melanomas (one dataset). Three of these datasets (one each for BCC, melanoma, and any malignant condition) were derived from one study which also performed a direct comparison with dermoscopy. Studies were of moderate to poor quality providing inadequate descriptions of participant selection, thresholds used to make cytological and histological diagnoses, and blinding. Reporting of patients’ prior referral pathways was particularly poor, as were descriptions of the cytodiagnostic criteria used to make diagnoses. No studies evaluated the use of exfoliative cytology as a primary diagnostic test for detecting BCC or other skin cancers in lesions suspicious for skin cancer. Pooled data from seven studies using standard cytomorphological criteria (but various stain methods) to detect BCC in patients with a high clinical suspicion of BCC estimated the sensitivity and specificity of exfoliative cytology as 97.5% (95% CI: 94.5 to 98.9%) and 90.1% (95% CI: 81.1 to 95.1%) respectively. When applied to a hypothetical population of 1000 clinically suspected BCC lesions with a median observed BCC prevalence of 86%, exfoliative cytology would miss 21 BCCs and would lead to 14 false positive diagnoses of BCC. No false positive cases were histologically confirmed to be melanoma. Insufficient data are available to make summary statements regarding the accuracy of exfoliative cytology to detect melanoma or cSCC, or its accuracy compared to dermoscopy. Authors' conclusions: The utility of exfoliative cytology for the primary diagnosis of skin cancer is unknown, as all included studies focused on the use of this technique for confirming strongly suspected clinical diagnoses. For the confirmation of BCC in lesions with a high clinical suspicion, there is evidence of high sensitivity and specificity for exfoliative cytology. Since decisions to treat low risk BCCs are unlikely in practice to require diagnostic confirmation given that clinical suspicion is already high, exfoliative cytology might be most useful for cases of BCC where the treatments being contemplated require a tissue diagnosis (e.g. radiotherapy). The small number of included studies, poor reporting and varying methodological quality means that no strong conclusions can currently be drawn to guide clinical practice. Despite insufficient data on the use of cytology for cSCC or melanoma, it is unlikely that cytology would be useful in these scenarios since preservation of the architecture of the whole lesion that would be available from a biopsy provides crucial diagnostic information. Given the paucity of good quality data, appropriately designed prospective comparative studies may be required to evaluate both the diagnostic value of exfoliative cytology by comparison to dermoscopy, and its confirmatory value in adequately reported populations with a high probability of BCC scheduled for further treatment requiring a tissue diagnosis.